2014
DOI: 10.1001/jamapediatrics.2013.3974
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathology and Its Risk and Protective Factors in Hearing-Impaired Children and Adolescents

Abstract: Literature on psychopathology in hearing-impaired children and adolescents is scarce and sometimes inconsistent. To define a more precise occurrence of psychopathology, more studies are needed. These studies should have a longitudinal design to draw firmer conclusions on causality. Hopefully, this will lead to more knowledge in the future to help and support each hearing-impaired individual.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
69
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(78 citation statements)
references
References 63 publications
5
69
0
1
Order By: Relevance
“…Introduction health problems have been observed for those with multiple health problems [12], communication problems [2,6,8,10], and intellectual impairments [11][12][13].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Introduction health problems have been observed for those with multiple health problems [12], communication problems [2,6,8,10], and intellectual impairments [11][12][13].…”
mentioning
confidence: 99%
“…A further limitation of previous research has been the focus on children with severe hearing loss, for example those recruited from clinics or special schools [11]. The use of standard decibel cut-off criteria in audiological and epidemiological research is widespread, with the definition of disabling hearing loss in children being ≥30dB according to the World Health Organization [18] and ≥40dB according to many national newborn hearing screening programs [19].…”
mentioning
confidence: 99%
“…More common are comparative studies for children with hearing loss. These studies suggest that the prevalence rates of mental health problems among deaf and hard-of-hearing children are two to four times higher than the rates among children without hearing loss [3][4][5][6]. For example, Fellinger et al [3] reported that the overall point and lifetime prevalence rates for psychiatric disorders were 32.6 and 45.3%, respectively, for a sample of 95 Austrian students aged 6-16 years with a hearing loss of minimum 40 decibel (dB).…”
Section: Introductionmentioning
confidence: 99%
“…Another factor discussed is the mode of communication used (i.e., sign language versus spoken language). Some studies have reported that the use of spoken language has better outcomes than the use of sign language, whereas other studies have reported no difference with regard to risk of additional disabilities (for a review see Theunissen et al [6]). Finally, the degree of hearing loss has also been discussed with regard to risk of additional disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Children with permanent childhood hearing loss (PCHL) are at risk of developing emotional and behaviour difficulties (EBD) (Stevenson, Kreppner, Pimperton, Worsfold, & Kennedy, 2015; Theunissen et al., 2014). As a group, these children also experience difficulties with expressive and receptive language development (Pimperton & Kennedy, 2012) and the acquisition of reading (Lederberg, Schick, & Spencer, 2013; Moeller, Tomblin, Yoshinaga‐Itano, Connor, & Jerger, 2007), particularly reading comprehension (McCann et al., 2009; Wauters, Van Bon, & Tellings, 2006).…”
Section: Introductionmentioning
confidence: 99%